Dynamic collaboration between small- and medium-sized enterprises from highly dissimilar markets. Issue 2 (April 2021) - Wang, Miaomiao; Mühlbacher, Hans; Wittmann, Xinhua; Perrett, Pieter
Abstract: Emerging markets have created significant opportunities for European small- and medium-sized enterprises (SMEs). Highly dissimilar market contexts compared to traditional markets and missing resources present substantial barriers to successfully serve those markets. Collaborative partnerships with local SMEs can help to overcome the barriers. Knowledge on how SMEs can develop lasting collaborative relationships in highly dissimilar contexts is scarce. This research investigates which factors influence the stability of more informal collaborative partnerships of Central European SMEs with SMEs located in China. A qualitative analysis of four cases confirms the importance of complementarity of partner resources, working well together based on mutual trust and commitment, shared sensemaking, and the balanced consideration of partner interests. Mutual learning and adaptation in iterative steps to enhance shared sensemaking and seeing differences in interpretation and behavior arising from contextual dissimilarity as opportunities instead of threats turn out to be SME-specific factors essential for building stable informal collaborative relations.